The Kepler conjecture the Hales- Ferguson proof by Thomas Hales, Samuel Ferguson - Lagarias, Jeffrey C. 1949-.; Ferguson, Samuel; SpringerLink (Online service). (New York Birkhäuser, 2011)
The Kepler conjecture, one of geometry's oldest unsolved problems. The Kepler conjecture states that the densest packing of three-dimensional Euclidean space by equal spheres is attained by the cannonball packing. This book centers around six papers, presenting the detailed proof of the Kepler conjecture.
Pt. 1. Introduction and survey -- pt. 2. Proof of the Kepler conjecture -- pt. 3. A revision to the proof of the Kepler conjecture -- pt. 4. Initial papers of the Hales program.
Electronic reproduction.
Keywords: Kepler's conjecture; Mathematics; Discrete groups; Convex and Discrete Geometry; Electronic book